Pertumbuhan Kelinci (Lepus spp.) Setelah Pemasangan Implan Stainless Steel AISI 316L - Wicaksono, Wisnu Adi; Tana, Silvana; Mardiati, Siti Muflichatun (Bioma : Berkala Ilmiah Biologi, 2016)
A lot of accidents can cause fractures/cracks, especially in the thigh bone. Bone fractures/cracks can be overcome through implants installation (implantation) particularly on the part of the femur. A test take the implant integration process about 4-6 week. Research on animals is performed the rabbit (Lepus spp.) implantation of stainless steel AISI 316L. The implantationof stainless steel AISI 316L implant was on the right femur between thigh bone and sceletal muscle, that was observed for 1,5 months. Parameters observed in this research were body weight gain, feed consumption, conversion of feed, and drinking consumption. Test used is t two test samples independent two sides with take samples 5 control and 5 treatment stainless steel AISI 316L. The results show the stainless steel AISI 316L implantsignificant differences body weight gain, feed consumption, and drinking consumption,but no significant different feed conversion. The conclusion is an implant stainless steel AISI 316L influence body weight gain rabbits after implantation for 1.5 months.Â Keywords: Rabbit, stainless steel AISI 316L, growth, body weight